Local Pathways to the National Leadership?: International Perspectives on Southeast Asia’s Presidential Democracies - Villanueva Ruiz, Karl Emmanuel (Policy & Governance Review, 2025)
This study analyzed how local leaders with no prior experience in countrywide politics could win national elections, focusing on Jejomar Binay and Joko Widodo in Southeast Asia's unitary presidential states: the Philippines and Indonesia. This study aims to contribute to the scant literature on outsider candidates and local-to-national leadership transitions. Using public administration theories on populism, participatory governance, and decision making, we propose a theoretical framework for analyzing these electoral triumphs. It is noteworthy that while past leaders experienced in national politics, the military, or business typically won high-level positions in these two countries, they did not. In this context, this study used qualitative methods (documentary research and thematic analysis of academic sources, communications, and campaign approaches) to examine local politicians' victories in their countries' highest echelons of power.